Sexual Dimorphism in Alpha Space: II The Differences Between Sexes in Some Indicators of Anxiety - Momirović, Konstantin; Hošek , Ankica; Kron, Leposava (Zbornik Instituta za kriminološka i sociološka istraživanja, 2005)
Random sample of 1332 subjects, age of 18, 666 male and 666 female, were tested by standard version of Alpha-test from battery KON6 that was made in order to estimate disturbances of conative functions of anxiety quality which are the consequences of dysfunction of system for regulation and control of defense reactions. The differences between male and female subjects were analyzed by canonical discriminative analysis after transformation of results in partial image form. The female subjects had systematically higher results on all indicators of anxiety so the distance of centroids of sexes on discriminative function was almost 1.2 standard deviation of that function. Therefore, the coefficient of separation of sexes in image space, defined by vectors of anxiety, reached the value of almost 0.6. and that is until now the highest obtained coefficient of separation of men and women in conative space. The biggest contribution to separation of sexes had the classical symptoms of anxiety associated with astenic modality of nervous system functioning.